Transcriptome analysis reveals chrysanthemum flower discoloration under high-temperature stress - Shi, Zhenjie; Han, Xiaoying; Wang, Guohui; Qiu, Jing; Zhou, Li-jie; Chen, Sumei; Fang, Weimin; Chen, Fadi; Jiang, Jiafu (Frontiers in Plant Science, 2022)
Temperature is an important environmental factor affecting plant anthocyanin synthesis. High temperatures are associated with decreased anthocyanin pigmentation in chrysanthemum. To reveal the effects of high temperature on anthocyanin biosynthesis in chrysanthemum, ray florets of the heat-sensitive cultivar ‘Nannong Ziyunying’ (ZYY) were subjected to RNA sequencing. A total of 18,286 unigenes were differentially expressed between the control and treatment groups. Functional annotation and enrichment analyses of these unigenes revealed that the heat shock response and flavonoid pathways were significantly enriched, suggesting that the expression of these genes in response to high temperature is associated with the fading of chrysanthemum flower color. In addition, genes related to anthocyanin synthesis and heat shock response were differentially expressed under high-temperature stress. Finally, to further investigate the molecular mechanism of discoloration under high-temperature stress and facilitate the use of marker-assisted breeding for developing novel heat-tolerant cultivars, these results were used to mine candidate genes by analyzing changes in their transcription levels in chrysanthemum.